The Influence of Consumer Perceptions and Attitudes towards Online Purchasing Decisions through Motivation on the Bukalapak Marketplace during the Covid-19 Pandemic (Study on Bukalapak Marketplace Consumers in Yogyakarta) - Iswandi, Anas; Istanto, Yuni; Pujiharjanto, Ambar (Journal of Business Innovation and Research, 2022)
This study was made to examine the influence of consumer perceptions and attitudes towards online purchasing decisions through motivation on the Bukalapak marketplace during the covid 19 pandemic, this research was applied to Bukalapak consumers in Yogyakarta.  Based on the population and the selected sample, the sampling technique in this study uses the Non-Probability Sampling method, which is a sampling technique that does not provide equal opportunities or opportunities for each element or member of the population to be selected as samples. The considerations in taking the sample selected in this study were: having made a purchase at the Bukalapak marketplace during the Covid-19 pandemic, being in Yogyakarta when making a purchase and being at least 17 years old when making a purchase. The sample size that will be taken in this study is 100 respondents. The data taken is then processed using SmartPLS 3.2.9 software. And the results of this study are all independent variables have a significant positive effect on repurchase decisions.